A delay in flap coverage of open midshaft tibia fractures increases complications: A retrospective study - Ahmed Mahmoud; Jarrod Younger; Emily Morris; Matthew Hope (Journal of Orthopaedics, Trauma and Rehabilitation)
Background: This retrospective study aimed to assess whether delaying flap coverage in open midshaft tibia fractures leads to higher infection rates. Methods: Patients were recruited retrospectively from a tertiary trauma database between 2012 and 2020. Patients included were over 18-years old and had an open tibia fracture that required flap coverage with at least 6 months follow-up. The collected complications were deep infections, aseptic non-union, flap failure and revision surgery. Results: Group-A ( n = 18) and Group-B ( n = 37) were analysed. Deep infections rate was 6% in Group-A and 38% in Group-B which was significantly different, χ 2 (1, N = 55) = 6.4, p = 0.01. The rate of revision surgery was 17% in Group-A and 54% in Group-B and was significant, χ 2 (1, N = 55) = 7, p = 0.008. Binary logistic regression showed that Group-B were 10 times more likely to develop a deep infection (95% confidence interval 1.2–83, p = 0.034). Conclusion: Delaying soft tissue coverage of open tibia fractures for over a week increases the risk of deep infection and revision surgery.